Pengaruh Literasi Keuangan, Gaya Hidup dan Pengendalian Diri Terhadap Perilaku Konsumtif Mahasiswa FEB Universitas Muhadi Setiabudi - Anesa Sintya Wati; Indah Dewi Mulyani; Yenny Ernitawati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research was conducted to determine the influence of financial literacy, lifestyle and self-control on the consumer behavior of FEB Muhadi Setiabudi University students. This research method is a quantitative method, by collecting respondent data by distributing questionnaires to students using gform. The population of this study was 492 students. Using the Slovin formula, the sample results were 85 students. The sampling technique uses nonprobability sampling with a purposive sampling method, data analysis tools use SPSS 25. The results of this study state: 1) Financial literacy (X1) partially does not have a significant influence on consumer behavior, 2) Lifestyle (X2) partially partially has a significant effect in a positive direction on consumptive behavior, 3) Self-control (X3) partially has a significant effect in a negative direction on consumptive behavior and 4) simultaneously the variables of financial literacy, lifestyle and self-control have an effect on consumptive behavior.